2018
DOI: 10.12688/gatesopenres.12837.1
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of PCV13 vaccine coverage using a repeated cross-sectional household survey in Malawi

Abstract: The 13-valent pneumococcal conjugate vaccine (PCV13) was Background: introduced in Malawi from November 2011 using a three dose primary series at 6, 10, and 14 weeks of age to reduce -related Streptococcus pneumoniae diseases. To date, PCV13 paediatric coverage in Malawi has not been rigorously assessed. We used household surveys to longitudinally track paediatric PCV13 coverage in rural Malawi.Samples of 60 randomly selected children (30 infants aged 6 weeks Methods: to 4 months and 30 aged 4-16 months) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
1
3
1
Order By: Relevance
“…Similar to the 2012–2014 findings from the Lilongwe cross-sectional household survey, 6 our data show lower reported vaccination rates among enrolled ITIP children compared to the data from the Malawi Ministry of Health national vaccination coverage reports. 7 Differences in methods and systems of data collection could contribute to these differences.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Similar to the 2012–2014 findings from the Lilongwe cross-sectional household survey, 6 our data show lower reported vaccination rates among enrolled ITIP children compared to the data from the Malawi Ministry of Health national vaccination coverage reports. 7 Differences in methods and systems of data collection could contribute to these differences.…”
supporting
confidence: 83%
“…In an assessment of PCV13 vaccine coverage using a repeated cross-sectional household survey to longitudinally track pediatric PCV13 coverage in rural Lilongwe, Malawi, a total of 8,562 children were surveyed in 6 surveys, and showed that despite large increases in two- and three-dose coverage among age-eligible children between March 2012 and June 2014, PCV13 coverage was consistently delayed and did not meet the Malawi Ministry of Health one-year three-dose 90% coverage target. 6 This is in contrast to the Malawi Ministry of Health national vaccination coverage reports which showed the percentage of surviving infants who received the third doses of the Hib conjugate vaccine and PCV13 in 2018 to be 92% for both these vaccines. 7…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Although great improvements have been made, our results and other existing evidence shows that by April 2014, PCV coverage did not meet the Malawi Ministry of Health threedose coverage target of 90% before 12 months. Our nationally representative study of children aged 1-36 months estimated that 77.0% of children had received all 3 PCV doses, less than the 86.0% estimated by Bondo et al [13], in rural children only, in one area (Kabadula) of one district (Lilongwe) of Malawi, aged between 6 weeks and 16 months. This could be explained by this studies findings in univariable logistic regression analysis that rural children have 0.82 reduced odds of receiving all 3 PCV vaccinations when compared to urban (p = 0.003, CI 0.71-0.93, however in multivariable regression there was no difference found, perhaps because of confounding of rural dwelling with other explanatory variables e.g.…”
Section: Pcvcontrasting
confidence: 56%
“…Malawian coverage estimates for all 3 PCV doses by 12 months old from data collected between 2012-2014 vary from 86% [13] 76% [7] increasing to 89.2% in 2015 [14] all just below the target for full immunisation set at >90% [15]. Munthali [16] stated that in Malawi it is considered the responsibility of a child's mother to ensure they are vaccinated.…”
Section: Introductionmentioning
confidence: 99%